Cellular and Molecular Mechanisms of Anterior Chamber-Associated Immune Deviation (ACAID): What We Have Learned from Knockout Mice - Vendomèle, Julie; Khebizi, Quentin; Fisson, Sylvain (Frontiers in Immunology, 2017)
Anterior chamber-associated immune deviation (ACAID) is a well-known phenomenon that can occur after an antigen is introduced without any danger signal into the anterior chamber of a murine eye. It is reported to lead to an antigen-specific immune deviation throughout the body. Despite the relatively little evidence of this phenomenon in humans, it has been suggested as a potential prophylactic strategy in allograft rejections and in several autoimmune diseases. Cellular and molecular mechanisms of ACAID have been explored in different murine models mainly as proofs of concept, first by direct analyses of immune components in normal immunocompetent settings and by cell transfer experiments. Later, use of knockout (KO) mice has helped considerably to decipher ACAID mechanisms. Several factors raise questions about the reliability and validity of studies using KO murine models, however. This mini-review summarizes results obtained with KO mice and discusses their advantages, their potential weaknesses, and potential methods for further progress.